2009
DOI: 10.1051/0004-6361/200912757
|View full text |Cite
|
Sign up to set email alerts
|

Radial distribution of the multiple stellar populations in $\mathsf{\omega}$ Centauri

Abstract: Aims. We present a detailed study of the radial distribution of the multiple populations identified in the Galactic globular cluster ω Cen. Methods. We used both space-based images (ACS/WFC and WFPC2) and ground-based images (FORS1@VLT and WFI@2.2m ESO telescopes) to map the cluster from the inner core to the outskirts (∼20 arcmin). These data sets have been used to extract high-accuracy photometry for the construction of color−magnitude diagrams and astrometric positions of ∼900 000 stars. Results. We find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
109
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 76 publications
14
109
4
1
Order By: Relevance
“…of MpIII stars, which has been shown to be more centrally concentrated in the cluster (Bellini et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…of MpIII stars, which has been shown to be more centrally concentrated in the cluster (Bellini et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, fainter than M B ∼ 5.7, isochrones for the "standard" and the "extreme" heavy-element mixtures are essentially identical when the same values of Y and [Fe/H] ZAHB loci Figure 2. Comparison of several ZAHB loci for the indicated properties with the horizontal-branch stars in ω Cen having M B < 3.2 (from Bellini et al 2009) on the assumption of the reddening and distance modulus that were assumed in the previous figure, as noted. As mentioned in the text, the predicted colors had to be increased by +0.04 mag in order for the models to reproduce the HB population in the blue tail satisfactorily.…”
Section: Color-magnitude Diagram Considerationsmentioning
confidence: 94%
“…Further studies on MSPs have shown that they exhibit different spatial (ω Cen Bellini et al 2009;several GCs Lardo et al 2011;47 Tuc Nataf et al 2011;M15 Larsen et al 2015) and dynamical signatures (47 Tuc Richer et al 2013 andKučinskas, Dobrovolskas &Bonifacio 2014). However, Dalessandro et al (2014) found that the different populations in NGC 6362 share the same radial distribution which is the first evidence of fully spatially mixed MSPs ever observed in a GC.…”
Section: Introductionmentioning
confidence: 92%